Evaluasi Program Paket C Menggunakan Model Evaluasi CIPP di PKBM Melati Kabupaten Enrekang - Yulianis; Arif Efendi As; Nurwafiqah Amirah Budi; Baharuddin; Muhammad Hatta (Mataram University, 2026)
Although various studies have evaluated the Package C Program using the CIPP model, most studies focused on general aspects of program implementation and were conducted in different locations. To date, there are not many studies that specifically evaluate the Package C Program at PKBM Melati, Enrekang Regency, by comprehensively examining the context, input, process, and product aspects according to the conditions and needs of the local community. This study aims to evaluate the implementation of the Package C Program at PKBM Melati, Enrekang Regency using the CIPP (Context, Input, Process, Product) evaluation model. The Paket C Program is one of the equivalency education services intended for people who are unable to attend formal education; therefore, program evaluation is necessary to determine the level of success and identify supporting and inhibiting factors. This study employed a qualitative evaluative approach involving PKBM managers, tutors, and learners as research subjects. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that in the context aspect, the implementation of the Paket C Program was in accordance with community needs for equivalency education services. In the input aspect, the availability of human resources, facilities, curriculum, and funding had supported program implementation although several limitations still existed. In the process aspect, learning activities had been carried out according to plan through face-to-face learning and assignments, but learner participation had not been fully optimal. In the product aspect, the program showed positive results in increasing community opportunities to obtain senior high school equivalency certificates as well as improving learners’ knowledge and skills. In general, the Paket C Program at PKBM Melati Enrekang Regency has been implemented fairly well, but improvements are still needed in facilities, learner discipline, and learning innovation.